Too exhausted to see the truth: Ego depletion and the ability to detect deception. (17th August 2012) - Reinhard, Marc‐André; Scharmach, Martin; Stahlberg, Dagmar
<x xml:space="preserve">Abstract</x> In two experiments, recent findings showing the detrimental role of regulatory depletion in decision making are extended to the field of deception detection. In both experiments, the state of ego depletion was induced by having judges inhibit versus non‐inhibit a dominant response while transcribing a text. Subsequently they judged true or deceptive messages of different stimulus persons with regard to their truthfulness. In both experiments, ego‐depleted judges scored significantly lower on detection accuracy than control judges. Signal detection measures showed that this effect was not due to differences in judgmental bias between the two conditions. In Experiment 2, it was shown that the lower detection accuracy in the state of ego depletion was due to a feeling of difficulty of relying on verbal content information. Practical implications of the current findings are discussed.